Revision of the Immaculatus Group of Culicoides Latreille (Diptera: Ceratopogonidae) from the Australasian Region with description of two new species - Bellis, G. A.; Dyce, A. L.; Gopurenko, D.; Mitchell, A. (Zootaxa, 2013)
The Immaculatus Group of Culicoides encompassing four species from Australia, New Caledonia, Fiji, Solomon Islands, New Guinea and the Malay archipelago is revised. A diagnosis for the group, descriptions of males and females of C. shivasi sp. n. and C. collessi sp. n., a description of the male of C. immaculatus Lee & Reye, a redescription of the female of C. immaculatus and a diagnosis of C. agas Wirth & Hubert together with keys for their specific determination are pre-sented. Specific separation of the morphologically similar C. shivasi and C. immaculatus is supported by DNA barcodes (mitochondrial cytochrome oxidase I or COI) and nuclear carbomoylphosphate synthetase (CAD) sequence data.